Vpliv laserskega površinskega pretaljevanja na zaostale napetosti v tankih ploščah - Grum, Janez (Kovine zlitine tehnologije, 1998)
Laser surface remelting is one of the best procedures for surface modification of ferrite-pearlite nodular irons. By this procedure it is possible to achieve a very high wear resistance of cast irons which can be compared with the wear resistance of surface hardened heat-treatable steels. The properties of the modified layer depend on the microstructure prior to heat treatment and on the amount of energy input transferred into the surface layer of the workpiece. The research work was focused on the study of residual stresses after laser surface remelting of ferrite-pearlite nodular iron 500-7 (ISO). The identification of residual stresses was performed using the relaxation method which consisted in measuring workpiece deformation.
Keywords: kaljenje; notranje napetosti; nodularna litina; laserska tehnika; plošče